1994
DOI: 10.1093/infdis/169.3.485
|View full text |Cite
|
Sign up to set email alerts
|

BK and JC Viruses in Human Immunodeficiency Virus Type 1-Infected Persons: Prevalence, Excretion, Viremia, and Viral Regulatory Regions

Abstract: Human polyomavirus BK (BKV) and JC (JCV) infections were examined in persons infected with human immunodeficiency virus type 1 (HIV-1). High frequencies of BKV (24%) and JCV viruria (16%) were detected by polymerase chain reaction (PCR). BKV viruria was not found in an immunocompetent control group, in contrast to a frequency of JCV viruria of 20%. The degree of HIV-induced immunodeficiency did not influence the prevalence of BKV viruria, in contrast to cytomegalovirus viruria, suggesting BKV reactivation is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
120
2
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 37 publications
14
120
2
4
Order By: Relevance
“…In a previous study in HIV-positive individuals, JCV and BKV sequences were found in 31.6% and 8.1%, respectively, of urine samples, whereas the positive test rate was 22.8% for JCV and as high as 51.1% for BKV in PBMCs (Sundsfjord et al 1994).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In a previous study in HIV-positive individuals, JCV and BKV sequences were found in 31.6% and 8.1%, respectively, of urine samples, whereas the positive test rate was 22.8% for JCV and as high as 51.1% for BKV in PBMCs (Sundsfjord et al 1994).…”
Section: Discussionmentioning
confidence: 71%
“…Peripheral blood mononuclear cells (PBMC) are a second important site of BKV latency. Compared to healthy subjects, there is an increased incidence of viruria in human immunodeficiency virus (HIV)-infected individuals, ranging from 20-44% in most studies (Markowitz et al 1993, Sundsfjord et al 1994, Degener et al 1997, Behzad-Behbahani et al 2004.…”
mentioning
confidence: 99%
“…Currently, a reduction of immunosuppressive therapy is effectively used to decrease viral replication in PVN patients suggesting that a functional immune system is critical in controlling BKV replication and pathology (11). The incidence of BKV reactivation also increases in many other groups of immunocompromised individuals (12)(13)(14)(15). Some work has focused on dissecting which components of the immune system control BKV replication.…”
mentioning
confidence: 99%
“…Estudios previos en pacientes sanos habían mostrado prevalencias muy diversas que oscilaron entre 7% y 92% en muestras de leucocitos 13 . En pacientes inmunocomprometidos también se ha determinado porcentajes diversos entre 4,7% en países nórdicos y 25% en Italia con técnicas más recientes 14,15 ; no puede excluirse la posibilidad de que la mejora en la sensibilidad de las técnicas de diagnóstico haya sido un factor relevante en la obtención de datos tan disímiles. Por otro lado, la mayor parte de estudios se ha focalizado en la búsqueda de genoma viral en muestras de orina, donde presuntamente se estaría detectando partículas virales; la búsqueda en leucocitos periféricos, tal como en este trabajo, está más focalizado en la búsqueda de genomas persistentes en células, donde no necesariamente está habiendo replicación activa, pero que podrían llevar a una reactivación posterior.…”
Section: Discussionunclassified